DETERMINASI MINAT PENGGUNAAN M-BANKING: KEMUDAHAN, KEPERCAYAAN, MANFAAT DAN FITUR LAYANAN - Silvia Avira Silvia Avira; Rofi’ah; Endang Setyaningsih; Suryandari Setyo Utami; Budiasih (Jurnal Aplikasi Perpajakan, 2026)
The rapid development of digital technology in the era of the Fourth Industrial Revolution has significantly transformed various sectors, including the banking industry. Today, Generation Z increasingly prioritizes convenience and speed in various aspects of life, particularly in conducting financial transactions. This study aims to analyze the influence of perceived ease of use, trust, perceived usefulness, and service features on Generation Z's intention to use the BCA mobile banking application, as well as to identify the most dominant factor influencing their intention to use the application. The analytical methods employed in this study include multiple linear regression analysis, the t-test (partial test), the F-test (simultaneous test), and the coefficient of determination (R²). The research data were collected through a questionnaire, with 100 valid responses obtained from the respondents. The sampling technique used was non-probability sampling with a purposive sampling approach. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results indicate that perceived ease of use, trust, perceived usefulness, and service features have both simultaneous and partial significant effects on Generation Z's intention to use BCA mobile banking. Among these variables, service features were found to be the most dominant factor influencing the intention to use the BCA mobile banking application.